"Disloyal to Civilization": Metafiction as Protest in Gina Apostol's Gun Dealers' Daughter. (26th November 2018) - Milne, Leah
Abstract: This article posits that recent multi-ethnic, metafictional texts present writing as a form of ethnic identity formation and self-care. Specifically, I focus on Gina Apostol's novel, Gun Dealers' Daughter (2012), which won the PEN Open Book Award in 2013. Gun Dealers' Daughter opens up questions about postcolonial subjects who find themselves living in the nation that colonized their countries of birth, and what options are available to those who are made to feel like foreigners in their own homes. The article shows how the fictional protagonist, Sol, challenges conventional approaches to an autobiographical genre known as the talambuhay in order to fight for her status as a subject. Within her talambuhay, Sol uses frequent revision, retellings, indirection, and other forms of nonlinear writing to reveal US history's erasure of its imperialist actions in the Philippines, especially in the wake of the 1901 Balangiga Massacre. In doing so, Sol seeks out a space of national belonging that does hinge upon an obliteration of her culture, history, or identity. I highlight how impossible it is for postcolonial American subjects such as Sol to achieve the rational wholeness expected of American multicultural citizens, and the ways that writing provides solace and a form of protest for subjects who have few other means to make themselves heard. Written in a way that would be considered "incorrect" by those around her, Sol's talambuhay becomes a form of creative activism as well as a way to protect and care for herself.